Strategic sports planning in Malaysia and Qatar / Siti Nazariah Abdul Razak and Tajul Arifin Muhamad - Abdul Razak, Siti Nazariah; Muhamad, Tajul Arifin (Universiti Teknologi MARA, 2022)
In the '11th Malaysia Plan 2016-2020' targets sports and recreation for development fall under the Ministry of Youth and Sports. Each division and agency, as well as the Olympic Council has its own strategic plan. Somewhat differently, Qatar launched a sports plan, its Sports Sector Strategy 2011- 2016 (2011), under the 'Qatar National Vision 2030'. Both countries recently accounted for elite sporting performances at the 18th Asian Games in Jakarta-Palembang (2018). Malaysia won 7 gold medals and placed 14th overall. Qatar took 6 gold medals and 15th place. This article compares Malaysia and Qatar sports programs regarding vision, mission, strategies, outcomes and problems. A literature review and document analysis are herein offered with the hope of aiding Malaysia's Ministry of Youth and Sports to develop proactive strategies with excellent outcomes.